2015
DOI: 10.1038/srep08187
|View full text |Cite
|
Sign up to set email alerts
|

Truncation and activation of GSK-3β by calpain I: a molecular mechanism links to tau hyperphosphorylation in Alzheimer's disease

Abstract: Abnormal hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase 3β (GSK-3β) is a primary tau kinase that is most implicated in tau pathology in AD. However, the exact molecular nature of GSK-3β involved in AD is unclear. In the present study, we found that GSK-3β was truncated at C-terminus and correlated with over-activation of calpain I in AD brain. Truncation of GSK-3β was positively correlated with tau hyperphospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 68 publications
8
85
1
Order By: Relevance
“…Indeed, GR can be phosphorylated on several serine and threonine residues. 53 Calpain 1 is particularly involved in the activation of GSK-3β, 54 and in the maturation of p35 in p25 55 ( Figure 4A,F). 49,50 We first confirmed changed expression ratios of p(Ser9)GSK-3β/ GSK-3β and p(Tyr216)GSK-3β/GSK-3β 51 ( Figure 4A-C), reflecting an increase in GSK-3β activation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, GR can be phosphorylated on several serine and threonine residues. 53 Calpain 1 is particularly involved in the activation of GSK-3β, 54 and in the maturation of p35 in p25 55 ( Figure 4A,F). 49,50 We first confirmed changed expression ratios of p(Ser9)GSK-3β/ GSK-3β and p(Tyr216)GSK-3β/GSK-3β 51 ( Figure 4A-C), reflecting an increase in GSK-3β activation.…”
Section: Resultsmentioning
confidence: 99%
“…For example, D’Orsi and colleagues showed that calpain activation occurs downstream of mitochondrial engagement during excitotoxic apoptosis [55]. Additionally, in Alzheimer’s disease µ-calpain activates GSK-3β [56]. Because EPO signaling modulates kinase activity, including activating Akt and inhibiting GSK-3β [57], EPO may be impacting calpain activity by altering the balance of Akt/GSK-3β activation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Cdk5/p25 is responsible for tau hyperphosphorylation under pathological conditions, including in Alzheimer’s disease (AD) or frontotemporal dementia with Parkinsonism linked to chromosome 17 (FTDP-17), is still controversial; further studies are needed to provide a convincing link between calpain activation, Cdk5 hyperactivation and tau hyperphosphorylation [62]. Another link between calpain, tau hyperphosphorylation and AD is provided by calpain-mediated truncation of GSK-3β [6769]. Calpain truncates GSK-3β in its C-terminal domain, resulting in increased kinase activity; in human AD brain, GSK-3β truncation is correlated with tau hyperphosphorylation, tangle score and Braak stage [69].…”
Section: Opposite Roles Of Calpain-1 and Calpain-2 In Neuroprotectionmentioning
confidence: 99%
“…Another link between calpain, tau hyperphosphorylation and AD is provided by calpain-mediated truncation of GSK-3β [6769]. Calpain truncates GSK-3β in its C-terminal domain, resulting in increased kinase activity; in human AD brain, GSK-3β truncation is correlated with tau hyperphosphorylation, tangle score and Braak stage [69]. However, increasing Ser9 phosphorylation by inhibiting certain phosphatases, such as phosphatase 1/2A prevented calpain-mediated cleavage of GSK-3β [68], indicating that the relationship between calpain, GSK-3β and tau hyperphosphorylation is extremely complex.…”
Section: Opposite Roles Of Calpain-1 and Calpain-2 In Neuroprotectionmentioning
confidence: 99%